Direct Utilization of Photoinduced Charge Carriers to Promote Electrochemical Energy Storage - Ren, Yuanfu; Zhu, Ting; Liu, Yadong; Liu, Quanbing; Yan, Qingyu (Small (Weinheim an der Bergstrasse, Germany), 2021)
Electrochemical energy storage has been regarded as one of the most promising strategies for next‐generation energy consumption. To meet the increasing demands of urban electric vehicles, development of green and efficient charging technologies by exploitation of solar energy should be considered for outdoor charging in the future. Herein, a light‐sensitive material (copper foam‐supported copper oxide/nickel copper oxides nanosheets arrays, namely CF@CuOx@NiCuOx NAs) with hierarchical nanostructures to promote electrochemical charge storage is specifically fabricated. The as‐fabricated NAs have demonstrated a high areal specific capacity of 1.452 C cm−2 under light irradiation with a light power of 1.76 W, which is 44.8% higher than the capacity obtained without light. Such areal specific capacity (1.452 C cm−2) is much higher than that of the conventional supercapacitor structure using a similar active redox component reported recently (NiO nanosheets array@Co3O4‐NiO FTNs: maximum areal capacity of 623.5 mF cm−2 at 2 mA cm−2). This photo‐enhancement for charge storage can be attributed to the combination of photo‐sensitive Cu2O and pseudo‐active NiO components. Hence, this work may provide new possibilities for direct utilization of sustainable solar energy to realize enhanced capability for energy storage devices. Copper foam supported copper oxide/nickel copper oxides nanosheets arrays (CF@CuOx@NiCuOx NAs) are fabricated and presented in this work. Thanks to the photosensitivity of Cu2O and pseudocapacitive property of NiO, the as‐fabricated NAs exhibit a remarkable capacitance increase of 44.8% under light irradiation compared to that without light, suggesting their promising use in light‐sensitive transparent supercapacitors.